Exploring the Contribution of Dairy Cooperatives to the Economic and Social Sustainability of Dairy Farmers in Bilaspur District, Chhattisgarh (International Journal of Food and Nutritional Sciences, 2022)
The impact of dairy cooperatives on the long-term financial and social stability of Chhattisgarh's Bilaspur District dairy producers is the focus of this research. This study seeks to evaluate the impact of cooperative models on revenue creation, resource access, community development, and sustainability in relation to the dairy industry, which is crucial to rural people' lives. The research uses a mixed-methods approach, collecting data on the effects of cooperative membership via quantitative surveys and qualitative interviews with cooperative executives and dairy producers.